Frontiers of Combining Systems 7th International Symposium, FroCoS 2009, Trento, Italy, September 16-18, 2009, Proceedings - Ghilardi, Silvio; Sebastiani, Roberto (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the refereed proceedings of the 7th International Symposium on Frontiers of Combining Systems, FroCoS 2007, held in Trento, Italy, September 16-18, 2009. The 20 revised full papers presented were carefully reviewed and selected. The papers are organized in topical sections on combinations of logics, theories, and decision procedures; constraint solving and programming; combination issues in rewriting and programming as well as in logical frameworks and theorem proving systems.